Increased metabolic activity in the septum and habenula during stress is linked to subsequent expression of learned helplessness behavior - Mirrione, Martine M.; Schulz, Daniela; Lapidus, Kyle; Zhang, Samuel; Goodman, Wayne; Henn, Fritz A. (Frontiers in Human Neuroscience, 2014)
Uncontrollable stress can have a profound effect on an organism's ability to respond effectively to future stressful situations. Behavior subsequent to uncontrollable stress can vary greatly between individuals, falling on a spectrum between healthy resilience and maladaptive learned helplessness. It is unclear whether dysfunctional brain activity during uncontrollable stress is associated with vulnerability to learned helplessness; therefore, we measured metabolic activity during uncontrollable stress that correlated with ensuing inability to escape future stressors. We took advantage of small animal positron emission tomography (PET) and 2-deoxy-2[18F]fluoro-D-glucose (18FDG) to probe in vivo metabolic activity in wild type Sprague Dawley rats during uncontrollable, inescapable, unpredictable foot-shock stress, and subsequently tested the animals response to controllable, escapable, predictable foot-shock stress. When we correlated metabolic activity during the uncontrollable stress with consequent behavioral outcomes, we found that the degree to which animals failed to escape the foot-shock correlated with increased metabolic activity in the lateral septum and habenula. When used a seed region, metabolic activity in the habenula correlated with activity in the lateral septum, hypothalamus, medial thalamus, mammillary nuclei, ventral tegmental area, central gray, interpeduncular nuclei, periaqueductal gray, dorsal raphe, and rostromedial tegmental nucleus, caudal linear raphe, and subiculum transition area. Furthermore, the lateral septum correlated with metabolic activity in the preoptic area, medial thalamus, habenula, interpeduncular nuclei, periaqueductal gray, dorsal raphe, and caudal linear raphe. Together, our data suggest a group of brain regions involved in sensitivity to uncontrollable stress involving the lateral septum and habenula.